Development of Alluvial Fans of the Southern Slope of the North Hamrin Anticline - Hamid Al-Jubouri, Sahar Laith; Khalaf, Mohammed Najem (Journal of Tikrit University for Humanities, 2024)
Alluvial fans are sometimes called fan plains, foot plains, muddy or alluvial fans, and these fans arise at the transition areas between areas with steep slopes, such as mountain ranges, high hills, and plateaus, and the low areas adjacent to them. The development of alluvial fans can be subject to several trends based on environmental and human factors, as the shape evolves over time due to sedimentation and changing water flow pattern. The influence of the geological situation (structural, tectonic, rock diversity) and surface geomorphological processes (climatic and morphodynamic) have led to its formation and development and the formation of alluvial fans, and on this basis the idea of research emerged. The research focused on the characteristics of the development of alluvial fans, what is the most dominant factor in their construction, and the development of trends of the alluvial fans, which consisted of development based on the tectonic factor, development based on climate change, based on the distribution of secondary deposit points, and development according to waterway deposits. The study includes field studies, satellite visuals, a digital elevation model, and geographic information systems software. From the results of the research, it appeared that the slope of the surface in the basin played a role in the emergence and development of the fan, through its effect on the quantity and speed of water drainage and then its effect on the quantity and quality of sediments transported to the surface of the fan. Severe erosion (laminar, flume, and groove) also prevailed, where the rate of erosion was 4500 m/ km2 and came in large areas as a result of floods and torrents in the middle of the fans and in areas extending the water networks, due to the dominance of clay and marl formation in the middle of the alluvial fans.